Diversity of Rhizo-Bacteriome of Crocus sativus Grown at Various Geographical Locations and Cataloging of Putative PGPRs - Ambardar, Sheetal; Bhagat, Nancy; Vakhlu, Jyoti; Gowda, Malali (Frontiers in Sustainable Food Systems, 2021)
Earlier plant growth-promoting rhizobacteria (PGPRs) were isolated from the plants, by cultivation-based techniques and the interaction was mostly thought to be bilateral. The routine bilateral study, with no information on the associated microbiome, could be one of the reasons for the limited success of PGPRs in the field conditions. Keeping in view the role of PGPRs in rhizo-bacteriome on the growth and production of plants, the present study was aimed at studying the diversity of the rhizo-bacteriome of saffron grown across 3 geographical locations namely Kashmir, Kishtwar, and Bengaluru. Variation in the rhizo-bacteriome of saffron growing across 10 different sites from 3 geographical locations was studied using 16S rDNA amplicon metagenomic sequencing. 16 bacterial phyla, 261 genera, and 73 bacterial species were cataloged from all the rhizosphere samples. Proteobacteria was a dominant phylum in all the rhizosphere samples. Rhizo-bacteriome of saffron grown in Kishtwar was found to be significantly different from the rhizo-bacteriome of saffron grown in Kashmir and Bengaluru. Interestingly, the rhizo-bacteriome of saffron grown in Bengaluru was very similar to the saffron grown in Kashmir, thereby indicating that the rhizo-bacteriome in saffron is “plant driven” as the corm sown in Bengaluru were from Kashmir. Despite variation in rhizo-bacteriome, core rhizo-bacteriome in saffron was identified that was represented by 53 genera and 8 bacterial species belonging to 11 phyla irrespective of their geographical distribution. In addition, 21 PGPRs were reported for the first time from the saffron rhizosphere. The high-yielding saffron field Wuyan was found to have the highest number of PGPRs; this indicates that the presence of PGPR is important for yield enhancement than diversity. The two PGPR Rhizobium leguminosarum and Luteibacter rhizovicinus were reported from all the locations except Kishtwar that had escaped isolation in our previous attempts using cultivation-based techniques. It is being proposed instead of going for random isolation and screening for PGPRs from the plant rhizosphere, an alternate strategy using metagenomic cataloging of the rhizo-bacteriome community and cultivation of the dominant PGPR should be undertaken. This strategy will help in the selection of dominant PGPRs, specific to the plant in question